PENGARUH FREKUENSI DRESSING PASTA KALSIUM HIDROKSIDA TERHADAP PERTUMBUHAN BAKTERI ANAEROB DAN DERAJAT KEASAMAN PADA PERAWATAN SALURAN AKAR GIGI INSISIVUS DESIDUI NEKROTIK - , ANGELICA ISADORA J ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the necrotic pulp causes is anaerobic bacteria infection. Root canal therapy needs to be taken by biomechanical preparation, NaOCl irrigation and dressing with antibacterial agents, such as calcium hydroxide. The objective of this study was to evaluate the influence of calcium hydroxide paste to the growth of anaerobic bacteria and the acidity or alkalinity (pH) rate of the necrotic deciduous incisors root canals treatments. The study method is root canal treatments of 8 necrotic deciduous upper teeth. During the treatments, calcium hydroxide paste dressings were applied on the first, the eighth, the fifteenth, and the twentieth day. Anaerobic bacteria and pH examinations from the root canals were taken on before dressing, the eighth, the fifteenth, and the twentieth day. The results are 5 of 8 teeth found Actinomyces sp. The first day was found in 5 teeth (62,5%), the eighth day was found in 4 teeth (50%), the fifteenth day was found in 1 tooth (12,5%), and the twentieth day no anaerobic bacteria were found. Mean of root canal pH on the first day was 5,36, on the eighth day was 7,25, on the fifteenth day was 9,38, and on the twentieth day was 11,38. Friedman test results showed a significant increase in alkalinity over time dressing (p<0,05). It is concluded that anaerobic bacteria, Actinomyces sp. were found. The more calcium hydroxide frequencies were applied, the less anaerobic bacteria were found in the root canals. Increasing the frequency of calcium hydroxide paste dressing, increasing the value of the deciduous incisor root canals pH.